Hybrid repair of ascending aortic pseudoaneurysm. Issue 3 (1st February 2021) - Blitzer, David; Nguyen, Stephanie N.; Patel, Virendra; George, Isaac; Takayama, Hiroo
Abstract: For ascending aortic pseudoaneurysms with a large aortic entry site and thrombus burden, temporary stent‐graft placement at induction of circulatory arrest can prevent thrombotic complication.